2017
DOI: 10.1080/15569527.2016.1268150
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol/disulphide homeostasis in patients with basal cell carcinoma

Abstract: Thiol disulphide homeostasis in patients with basal cell carcinoma alters in the way that disulphide gets lower and thiols get higher. Thiol/disulphide level is likely to have a role in basal cell carcinoma pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 6 publications
7
38
1
1
Order By: Relevance
“…Demirseren et al evaluated dynamic TDH in patients with basal cell carcinoma, and found a significant reduction in disulfide levels and increased native thiol levels. In light of these findings, the authors concluded that TDH may be dysregulated in the proliferative phase of the disease [24]. In this study, native thiol levels did not differ significantly between patients with AV and the control subjects, while total thiol levels were found to be significantly lower in patients with AV.…”
Section: Discussioncontrasting
confidence: 40%
“…Demirseren et al evaluated dynamic TDH in patients with basal cell carcinoma, and found a significant reduction in disulfide levels and increased native thiol levels. In light of these findings, the authors concluded that TDH may be dysregulated in the proliferative phase of the disease [24]. In this study, native thiol levels did not differ significantly between patients with AV and the control subjects, while total thiol levels were found to be significantly lower in patients with AV.…”
Section: Discussioncontrasting
confidence: 40%
“…Thiol disulfide homeostasis in patients with basal cell carcinoma, psoriasis and seborrheic dermatitis has changed as the increased NT. It has been suggested that increased NT levels cause proliferation, whereas reduced NT along with the increased disulfide results in cell apoptosis [70][71][72].…”
Section: Dermatologic Disordersmentioning
confidence: 99%
“…The thiol-disulphide balance has been researched in a limited number of dermatoses (urticaria, basal cell carcinoma, atopic dermatitis) until now [9,10,18]. Demirsen et al carried out research on 34 patients with basal cell carcinoma and a group of 30 healthy individuals to determine the thiol-disulphide balance.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a statistically significant difference between the disulphide/native thiol and native thiol/total thiol ratios and the serum native thiol and disulphide levels between the patient and healthy groups. This established that the thiol-disulphide balance could be a factor in the pathogenesis of basal cell carcinoma [10]. In another study undertaken by Akbas et al, the thiol/disulphide homeostasis was examined in 53 patients with acute urticaria and 47 healthy individuals, and 57 patients with chronic spontaneous urticaria and 57 healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation